Nationwide Multicenter Survey for Current Status of Endoscopic Thyroidectomy in Korea - Park, Ki Nam (Clin Exp Otorhinolaryngol, 2015)
OBJECTIVES: We evaluated the current status of endoscopic thyroidectomy procedures in Korea in terms of indications, contraindications, advantages, disadvantages, complications, and limitations of each approach. METHODS: An email survey, consisting of 15 questions, was sent to 29 experienced endoscopic thyroidectomy surgeons. RESULTS: The most commonly used approach was the gasless transaxillary approach (66.7%), followed by the bilateral axillo-breast approach with gas insufflation (23.8%). The most common indication was less than 1 cm, single papillary thyroid cancer. The role of endoscopic thyroidectomy is not still established; some consider it a novel procedure (34.8%), others a transition to robotic thyroidectomy (34.8%). CONCLUSION: Our results shed light on the general consensus of opinions about endoscopic thyroidectomy, such as the advantages, disadvantages, complications, limitations, and even its future role.